Shape Memory Polyurethane Materials Containing Ferromagnetic Iron Oxide and Graphene Nanoplatelets - Urban, Magdalena (Materials (Basel), 2017)
Intelligent materials, such as memory shape polymers, have attracted considerable attention due to wide range of possible applications. Currently, intensive research is underway, in matters of obtaining memory shape materials that can be actuated via inductive methods, for example with help of magnetic field. In this work, an attempt was made to develop a new polymer composite—polyurethane modified with graphene nanoplates and ferromagnetic iron oxides—with improved mechanical properties and introduced magnetic and memory shape properties. Based on the conducted literature review, gathered data were compared to the results of similar materials. Obtained materials were tested for their thermal, rheological, mechanical and shape memory properties. Structure of both fillers and composites were also analyzed using various spectroscopic methods. The addition of fillers to the polyurethane matrix improved the mechanical and shape memory properties, without having a noticeable impact on thermal properties. As it was expected, the high content of fillers caused a significant change in viscosity of filled prepolymers (during the synthesis stage). Each of the studied composites showed better mechanical properties than the unmodified polyurethanes. The addition of magnetic particles introduced additional properties to the composite, which could significantly expand the functionality of the materials developed in this work.